The Effectiveness of Group Counseling Using the Behavior Contract Technique in Reducing Gadget Addiction and Improving Academic Self-Regulation among Students - Bambang BambangSuroto (Journal of Education and Teaching Learning, 2026)
This study aimed to examine the effectiveness of group counseling using a behavioral approach with a behavior contract technique in reducing gadget addiction and improving academic self-regulation among vocational high school students. The research employed a quasi-experimental design with a pretest–posttest control group design. Participants were 40 students selected through purposive sampling and divided into experimental and control groups. Data were collected using a gadget addiction scale and an academic self- regulation scale. The results indicated that descriptively, the experimental group showed greater improvement compared to the control group. However, the independent sample t- test revealed that the difference was not statistically significant at the 0.05 level. Despite this, the positive trend suggests that group counseling with behavior contract techniques has potential as an intervention strategy in school counseling services to address gadget addiction and enhance students’ academic self-regulation.